The curious and intricate case of the European Hediste diversicolor (Annelida, Nereididae) species complex, with description of two new species. Issue 1 (31st December 2022) - Teixeira, Marcos A. L.; Bakken, Torkild; Vieira, Pedro E.; Langeneck, Joachim; Sampieri, Bruno R.; Kasapidis, Panagiotis; Ravara, AscensÃO; Nygren, Arne; Costa, Filipe O.
Abstract : Past molecular studies using mtDNA sequences and alloenzymes signalled the existence of at least two cryptic species within the Hediste diversicolor morphotype, in European coasts. However, to this day, no new species descriptions have been made. In this study, we identified five completely sorted lineages using a multi-locus approach, including the mitochondrial DNA cytochrome oxidase I gene (COI-5P) and the nuclear markers ITS2 rRNA and 28S rRNA. The molecular data were complemented with morphometric measurements examined through multivariate statistical analysis and the incorporation of statistical dissimilarities. Apart from the Baltic Sea, where three of the lineages occur in sympatry, Hediste diversicolor comprises four deeply divergent allopatric lineages in the rest of Europe. They group populations from the NE Atlantic and part of the Western Mediterranean Sea; from the Tyrrhenian Sea; from the Adriatic and Ionian Sea; and, lastly, from the Caspian, Black and the northern Aegean Seas. The lineage from the Ionian Sea revealed low genetic distances compared with the one from the Adriatic Sea and lacked enough specimens for the morphometric analysis, preventing further conclusions about its independent status. Three independent morphometric clusters were identified mainly based on worm size, the distance between the anterior and posterior eyes, parapodia proportions and the length of several prostomial appendages. Two sympatric lineages present in the Baltic Sea, showed evidence of possible hybridization and lacked significant PCA morphometric variation between them. The two remaining lineages were formally described as new species, namely Hediste pontii sp. nov. (Adriatic Sea) and Hediste astae sp. nov. (northern Aegean, Caspian and Black Seas). These new species can now be formally recognized and used in biomonitoring or other relevant ecological studies. Finally, a neotype is defined for H. diversicolor, whose usage is restricted to the NE Atlantic lineage. http://www.zoobank.org/urn:lsid:zoobank.org:pub:948C73FC-B07F-40A3-B8FA-03B60DE2089D